2015
DOI: 10.3892/ol.2015.3976
|View full text |Cite
|
Sign up to set email alerts
|

Role of deregulated microRNAs in non-small cell lung cancer progression using fresh-frozen and formalin-fixed, paraffin-embedded samples

Abstract: Abstract. Non-small cell lung cancer (NSCLC) is responsible for the highest number of cancer-associated mortalities worldwide, and the five-year survival rate is <15% following the initial diagnosis. MicroRNAs (miRNAs) serve important functions in a number of human diseases, including cancer. The present study investigated the expression status, clinical relevance and functional role of miRNA in NSCLC. miRNA expression profiling was performed in lung adenocarcinoma and adjacent unaffected lung tissues using 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…In our previous study, we identified miR-363-3p was a potential tumor suppressor in lung cancer [22]. A previous study of liver cancer indicated that miR-363-3p can reduced tumorigenesis by inhibiting the G1 to S phase transition [11].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we identified miR-363-3p was a potential tumor suppressor in lung cancer [22]. A previous study of liver cancer indicated that miR-363-3p can reduced tumorigenesis by inhibiting the G1 to S phase transition [11].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA expression was represented by 2−ΔCT, where ΔCT = (CT MiRNA of case or control minus CT reference sample). SnRNA U6 was used as an endogenous control to normalize all samples …”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown that miRNAs participate in some cell signaling processes, including apoptosis, cell proliferation, and epithelial-to-mesenchymal transition [19, 20]. Quantification of miRNA expression can be performed even using relatively degraded samples, such as FFPE samples, in a PCR-based test (real-time PCR) [14, 21-23]. In this study, we used FFPE samples as well as snap-frozen samples (different quality of RNA) and examined the expression of several candidate miRNAs.…”
Section: Discussionmentioning
confidence: 99%